The role model effect in higher education. - Boulware, Jessica (Kansas State University, 2011)
This report provides review of the existing literature on the role model effect in higher education and identifies the methodological and conceptual issues that have complicated the research program before discussing how research on similar areas may provide insight into the relationship between female students and female faculty members. By examining the related literature on the determinants of college major, peer effects, and critical mass theory, the existing studies of role model effect can be interpreted as support for a more specified theory of the role model effect in higher education that highlights the importance of the gender composition of the course or field of study.
Keywords: Role model effect; STEM; Economics (0501)